PERMINTAAN DAN PENAWARAN DALAM MEMPENGARUHI PASAR (Studi Kasus di Pasar Bintoro Demak) (Universitas Islam Negeri Sunan Kudus, 2016)
The market is the place to accommodate the results of theproduction and sell them to those in need. Islam set so that thecompetition in the market is done with fair, every form that cancause the injustice is forbidden by Islam. Reduce weightsbanned because of goods sold with the same price for theamount less. Hide the flawed goods forbidden, because theseller was getting a good for a bad quality. Changed the drieddates with palms wet forbidden, because the quantity of wetdates when dry can be so does not match with the dried datesthat changed. For the community of Demak, Markets Bintoro isa parent market that has historical value. The market is knownas the shopping center the results of earth City Mayor sincecolonial times. Various trade activities done at the site.Discounted Rates the results of the earth which is high enoughin the place is the sale and purchase of staple food, especiallyrice. In the context of the request and the offer, kemanfaatanlahthat move the demand in the market Bintoro Demak. If thebenefit something very large, then the request will also belarger, so also on the contrary.